Synthesis of New Heterocyclic Amino Derivatives of Alantolactone and Their Cytotoxic Activity. (23rd October 2018) - Kumar, Ashish; Kumar, Dharmesh; Maurya, Antim K.; Padwad, Yogendra S.; Agnihotri, Vijai K.
Abstract : In this study, a series of new alantolactone (AL ) amino scaffolds (AL1 –AL13 ) had been synthesized and evaluated for in vitro cytotoxicity against three human cancer cell lines: human cervical cancer (SiHa), human epidermoid carcinoma (KB), and human lung cancer (A549). The compoundsAL 2, 4, 5, 7, and13 were found to be nearly as equally active asAL against three tested cell lines, whereasAL 1 and12 against SiHa cells. This study also provides a correlation on the structure activity relationship ofAL and derivatized analogues against tested cells. The retention of cytotoxicity with enhanced water solubility in derivatized amino adducts includingAL 1, 2, 4, 5, 7, 12, and13 indicates that these adducts can further be tested for the detailed in vivo safety and anticancer studies. Abstract :